1997
DOI: 10.1093/ajcn/65.2.512
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine alpha-ketoglutarate metabolism after enteral administration in burn patients: bolus compared with continuous infusion

Abstract: Ornithine alpha-ketoglutarate (OKG) has been successfully used as an enteral supplement in the treatment of catabolic states, including burn injury. However, specific questions remain unanswered concerning burn patients, including OKG metabolism and metabolite production, appropriate mode of administration, and dose. We thus performed a kinetic study and followed plasma ornithine and OKG metabolite concentrations on day 7 postburn in 42 (35 men, 7 women) consecutive burn patients aged 33 +/- 2 y with a mean (+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Our study design is different compared to the study of Vanderhoof et al [29]. Considering the findings of better glutamine plasma levels after a bolus compared to continuous administration of the glutamine precursor ornithine ketoglutarate [35], rats were given a glutamine 2 g/kg/day bolus by gavage in our study, in order to keep a defined supplementation of glutamine per day. During the first 3 days postoperatively, the ras ate <10 g of chow on an ad libitum basis per day.…”
Section: Discussionmentioning
confidence: 99%
“…Our study design is different compared to the study of Vanderhoof et al [29]. Considering the findings of better glutamine plasma levels after a bolus compared to continuous administration of the glutamine precursor ornithine ketoglutarate [35], rats were given a glutamine 2 g/kg/day bolus by gavage in our study, in order to keep a defined supplementation of glutamine per day. During the first 3 days postoperatively, the ras ate <10 g of chow on an ad libitum basis per day.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage-mediated phagocytosis is influenced by glutamine availability (11). Beneficial effects of the provision of glutamine (16) or its precursors (17) have been reported in patients submitted to surgery, radiation treatment or bone marrow transplantation or suffering from injury, sepsis or burns (18).…”
Section: Role Of Glutamine In Immune Functionmentioning
confidence: 99%
“…Metabolites of OKG regulate protein turnover. It was shown that bolus feeding was beneficial in comparison with the continuous infusion with regard to absorption and metabolism of OKG (Bricon et al, 1997).…”
Section: Discussionmentioning
confidence: 99%